Pengembangan Aplikasi Diagnosis Gejala Depresi pada Mahasiswa Fakultas Ilmu Komputer (Studi Kasus : Fakultas Ilmu Komputer Universitas Brawijaya) - Enggarsita Auliasin; Denny Sagita Rusdianto; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The application to diagnose depression symptoms in students is an application intended to help counseling counselors in providing services to students to conduct consultations. In diagnosing a good depression, a system that can diagnose depression is needed and can store data on students who have come to consult and build a structured consultation approach. However, counseling counselors have problems in their services. Every student who came they could not know the extent of depression that students experienced so it was not too clear how the solution was handled, and the lack of data storage of student recordings that had come to consult. These problems lead to a lack of understanding of students about the services they receive, due to the limited ability of counseling counselors. If this problem is not addressed, the counseling service process cannot run optimally. The solution to this problem is to develop an application for diagnosing web-based depressive symptoms that can help counseling counselors in carrying out their services in knowing what students complain about, knowing the symptoms of depression, learning the symptoms of various types of depression, storing the results of students who have registered. Research produces engineering needs, namely 37 functional requirements and 1 non-functional requirement. Implementation is done using the PHP programming language, the Model-View-Controller (MVC) design pattern, and the phpMyAdmin database.